(untitled) (Research, Society and Development, 2022)
Objective: To identify the main short and long-term clinical consequences of preeclampsia for pregnant women and what are the risk factors associated with this pathological condition. Methods: This is an narrative literature review, with articles published between 2016 and 2021, in Portuguese and English, with full text available. It was used as a guiding question: What is the relationship between risk factors and clinical complications in the face of the impacts of preeclampsia on the health of pregnant women? The literature search was carried out in October 2021, using the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS); Scientific Electronic Library Online (SciELO) and PubMed. The descriptors used were: “preeclampsia”, “preeclampsia”, “clinical manifestations of preeclampsia”, “preeclampsia clinical manifestation”, “symptoms of preeclampsia”, “preeclampsia symptoms”. Results: 18 (eighteen) articles that were within the established criteria were qualitatively selected. Discussion: the selected articles found that the earlier the causes and risk factors associated with preeclampsia are identified, the better the patient’s prognosis. Final considerations: The identification of risk factors favors early diagnosis and therapeutic intervention of preeclampsia, favoring the involution of the condition, otherwise the pregnant woman may develop significant clinical complications.